Leadership and agency in Ukraine-related discourse: Focus on press conferences and Twitter - Tereszkiewicz, Anna; Szczyrbak, Magdalena Adriana (de Gruyter Open, 2024)
This paper reports on a study into discursive leadership and agency construction in Ukraine-related political discourse, as exemplified by press conferences and Twitter. The material used in the analysis includes transcripts of press conferences and Twitter posts by three European politicians, i.e. Mateusz Morawiecki, Boris Johnson and Olaf Scholz, from the period between February and June 2022. The study investigates how the speakers construct leadership and agency in two different communicative settings and whether any differences can be noted between their respective styles. Drawing on Systemic Functional Grammar, the analysis examines different process and reference types, and illustrates their role in the projection of leadership and agency, as well as accounts for the impact of the communicative setting on linguistic choices. The study reveals that material processes are the most visible in both situational contexts, which indicates that the politicians emphasize the actions taken in response to the crisis. Regarding the types of reference (i.e. first-person singular and first-person plural), the analysis shows that first-person plural forms linked to international collectivity are the most salient in both settings. The findings suggest that underscoring responsiveness, competence and international cooperation are the dominant strategies of establishing discursive leadership and agency in crisis circumstances.
Vůdcovství a konání v diskurzu o Ukrajině: Zaměření na tiskové konference a Twitter
Keywords: discursive leadership; agency; Systemic Functional Grammar; press conference; Twitter; Ukraine; diskurzní vůdcovství; systémová funkční gramatika; tisková konference; Twitter; Ukrajina